2018
DOI: 10.1159/000487912
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine Inhibits Homocysteine-Mediated Autophagy via MIF/mTOR Signaling in Human Umbilical Vein Endothelial Cells

Abstract: Background/Aims: Genetic or nutritional deficiencies in homocysteine (Hcy)metabolism lead to the accumulation of Hcy and its metabolites in the blood. This can lead to hyperhomocysteinemia (HHcy), which is an independent risk factor for cardiovascular disease. Studies have shown that HHcy leads to endothelial dysfunction, a hallmark of atherosclerosis, which may explain this link. The precise mechanism remains unclear, but a strong possibility is excessive HHCy-induced autophagy. Autophagy has been better stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…It is similar to apoptosis; autophagic bodies in ECG- and EGCG-treated cells were significantly less than those in the solvent control group, and EGCG-treated cells produced even more autophagic bodies than did ECG-treated cells. During ischemia/reperfusion injury, oxidative stress may induce epithelial cell apoptosis [5053] and/or autophagy [51, 54, 55]. Autophagy is a widely existing metabolic and strictly regulated process, and excessive or deficient autophagy may contribute to pathogenesis [56].…”
Section: Discussionmentioning
confidence: 99%
“…It is similar to apoptosis; autophagic bodies in ECG- and EGCG-treated cells were significantly less than those in the solvent control group, and EGCG-treated cells produced even more autophagic bodies than did ECG-treated cells. During ischemia/reperfusion injury, oxidative stress may induce epithelial cell apoptosis [5053] and/or autophagy [51, 54, 55]. Autophagy is a widely existing metabolic and strictly regulated process, and excessive or deficient autophagy may contribute to pathogenesis [56].…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed in several different cell types that Hcy-induced cell injury by stimulating autophagy. For instance, human umbilical vein endothelial cells damaged by Hcy exhibit features of autophagic/lysosomal cell death accompanying with the higher expression levels of the autophagy-related genes Atg 5 and Beclin 1, greater degradation of LC3 I to LC3 II and the cytoplasmic autophagic vacuoles 16 . Zhao et al reported that Hcy treatment aggravated neuronal cell death, significantly increased the formation of autophagosomes and the expression of LC3B and Beclin 1 in the brain cortex after middle cerebral artery occlusion-reperfusion 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the key role of MCs in glomerular function, the Hcy-induced apoptosis of MCs may be an important factor in the development and progression of CKD. Hcy has been reported to affect cell viability and induce apoptosis in various cell types, such as neuronal cells, 8,9 vascular endothelial cells, 12,13 SMCs, 14 and podocytes. 28 In the present study, we found that the viability of MCs was clearly decreased with the increase of Hcy concentration from 50 to 1000 mmol L À1 .…”
Section: Discussionmentioning
confidence: 99%
“…6 Enhanced apoptosis is a universal nding in both clinical and experimental kidney diseases that involve the mesangium, which irreversibly affects the pool of MCs and leads to their disappearance from mesangium. 7 On the other hand, previous studies showed that Hcy could induce the apoptosis of neuronal cells, 8,9 cardiomyocytes, 10,11 vascular endothelial cells, 12,13 and smooth muscle cells (SMCs). 14 Interestingly, there is a similarity in the mechanism that Hcy could induce the apoptosis of these cell types by activating endoplasmic reticulum stress (ERS) and autophagy.…”
Section: Introductionmentioning
confidence: 99%